2001
DOI: 10.1054/bjoc.2001.2176
|View full text |Cite
|
Sign up to set email alerts
|

EBAG9/RCAS1 in human breast carcinoma: a possible factor in endocrine–immune interactions

Abstract: EBAG9 has been recently identified as an oestrogen responsive gene in MCF-7 human breast carcinoma cells. EBAG9 is identical to RCAS1, a cancer cell surface antigen possibly involved in immune escape. In this study, we examined the expression of EBAG9/RCAS1 in human breast carcinomas using immunohistochemistry and reverse transcription-polymerase chain reaction (RT-PCR). EBAG9 immunoreactivity was also associated with various clinicopathological parameters, including intratumoural infiltration of inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 40 publications
4
53
0
Order By: Relevance
“…EBAG9 has been shown to be expressed at a very low level in MDA-MB-231 cells without the addition of estrogen, and robustly expressed after estrogen treatment in ER␣ positive MCF-7 cells (15). When ER␣-positive breast cancer cells are treated with tamoxifen, the mRNA expression of both CATD and EBAG9 is repressed (35,36). MDA-MB-231 cells were grown in hormone free medium and stimulated with rWnt-5a or Foxy-5.…”
Section: Resultsmentioning
confidence: 99%
“…EBAG9 has been shown to be expressed at a very low level in MDA-MB-231 cells without the addition of estrogen, and robustly expressed after estrogen treatment in ER␣ positive MCF-7 cells (15). When ER␣-positive breast cancer cells are treated with tamoxifen, the mRNA expression of both CATD and EBAG9 is repressed (35,36). MDA-MB-231 cells were grown in hormone free medium and stimulated with rWnt-5a or Foxy-5.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Sonoda et al (1998) reported that RCAS1 was not detected in the normal uterine cervix or ovarian tissue, but strongly expressed in uterine endometrial adenocarcinomas, ovarian adenocarcinomas (Sonoda et al, 1996;Sonoda et al, 2000) and cervical squamous cell carcinomas. Recently, Suzuki et al (2001) reported that EBAG9 immunoreactivity was detected in 82 of 91 in breast carcinoma (90.1%), although it was not associated with clinicopathological parameters. Others reported that EBAG9 gene was consistently expressed in breast cancer cell line, and might play a specific role in early stages of breast carcinogenesis (Tsuneizumi et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Tumor size was measured weekly with a micrometer in two dimensions, and tumor volume was estimated according to the formula: (smallest diameter) 2 Â (longest diameter). When the volumes of tumors reached 300 mm 3 , siRNA duplexes (10 Ag) were injected directly into tumors twice every week, along with 4 AL of GeneSilencer (Gene Therapy System, San Diego, CA) dissolved in 0.1 mL of Opti-MEM (Life Technologies, Gaithersburg, MD). Mice were sacrificed 4 weeks after treatment.…”
Section: Methodsmentioning
confidence: 99%